Analisa Perbandingan Switch Mode Power Supply (SMPS) dan Transformator Linear Pada Audio Amplifier - Cholish Cholish; Rimbawati Rimbawati; Abdul Aziz Hutasuhut (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
The Advantages of electronics equipment requires the increased efficiency and technology to reduce the use of electrical energy. The electrical equipment in residential energy consumption is the dominant burden on electricity supply service. Audio Amplifier is a widely used household appliance in general based on the linear transformer. A Linear transformer has much deficiency such as dimensions of equipment and the use of technology control systems which less of good and large voltage drop. Because of that, the design of Switch Mode Power Supply (SMPS) model would be a replacement linear transformer. In this research, we will compare the performance of Linear Trafo with SMPS specification +/- 35VDC - 350W. By making modifications to SMPS on the transformer windings which could be seen as the significant comparison to the use of equipment.